2013
DOI: 10.1371/journal.pone.0079861
|View full text |Cite
|
Sign up to set email alerts
|

Microarray and RNAi Analysis of P450s in Anopheles gambiae Male and Female Steroidogenic Tissues: CYP307A1 Is Required for Ecdysteroid Synthesis

Abstract: In insects, the steroid hormone 20-hydroxyecdysone (20E) coordinates major developmental transitions. While the first and the final steps of 20E biosynthesis are characterized, the pathway from 7-dehydrocholesterol to 5β-ketodiol, commonly referred as the “black box”, remains hypothetical and whether there are still unidentified enzymes is unknown. The black box would include some oxidative steps, which are believed to be mediated by P450 enzymes. To identify new enzyme(s) involved in steroid synthesis, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…By contrast, Spo knockdown in Schistocerca gregaria and An. gambiae had no clear developmental phenotype despite reduced ecdysteroid production (Marchal et al ., ; Pondeville et al ., ). The incomplete development that we observed compared with the delayed development reported in other studies could be attributable to methodological variations in dsRNA delivery or biological compensatory effects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…By contrast, Spo knockdown in Schistocerca gregaria and An. gambiae had no clear developmental phenotype despite reduced ecdysteroid production (Marchal et al ., ; Pondeville et al ., ). The incomplete development that we observed compared with the delayed development reported in other studies could be attributable to methodological variations in dsRNA delivery or biological compensatory effects.…”
Section: Discussionmentioning
confidence: 97%
“…gregaria (Marchal et al, 2011), Holcocerus hippophaecolus (Zhou et al, 2013), An. gambiae (Pondeville et al, 2013) and T. castaneum (Parthasarathy et al, 2010). RNAi-mediated knockdown of Spo and Phantom in An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify new enzymes associated with the activity of 20E, a small‐scale microarray analysis was performed to compare the expression of P450 enzymes in active and inactive steroidogenic tissues. The analysis revealed that only three genes encoding P450 enzymes, cyp4g16 , cyp6n1 and cyp307a1 , are up‐regulated in the active steroidogenic tissues of both male and female mosquitoes, but only cyp307a1 is involved in steroidogenesis (Pondeville et al ., ).…”
Section: Other Transcriptomics Studies On An Gambiaementioning
confidence: 97%
“…Blood digestion provides amino acids to the fat body for the production of yolk proteins, which are then packaged into primary oocytes that develop into mature eggs. Studies conducted primarily with Aedes aegypti indicate that ecdysteroid hormone (ECD) produced by the ovaries is the primary factor that activates the fat body to synthesize yolk proteins (Attardo et al, 2005; Baldridge and Feyereisen, 1986; Gulia-Nuss et al, 2012; Gulia-Nuss et al, 2015; Pondeville et al, 2008; 2013; Roy et al, 2015). Prior studies further show that ovaries produce ECD in response to insulin-like peptides (ILPs) and ovary ecdysteroidogenic hormone (OEH), which are released from neurosecretory cells in the brain within a few hours after females consume a blood meal (Riehle and Brown, 1999; Riehle and Brown, 2002; Gulia-Nuss et al, 2011; Dhara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%